Answer:
280.6 ![m^2](https://tex.z-dn.net/?f=m%5E2)
Step-by-step explanation:
<u>find the length of each side:</u>
you're only given h = 9 m
the formula for h is
, where a is a side length of the hexagon
plug h in:
![9=\frac{\sqrt{3}}{2}*a\\\\a=9*\frac{2}{\sqrt{3}}\\\\](https://tex.z-dn.net/?f=9%3D%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D%2Aa%5C%5C%5C%5Ca%3D9%2A%5Cfrac%7B2%7D%7B%5Csqrt%7B3%7D%7D%5C%5C%5C%5C)
a ≈ 10.392 m
<u>now find the area of a triangle:</u>
1/2 (10.392)(9) = 46.764 ![m^2](https://tex.z-dn.net/?f=m%5E2)
multiply that by 6 and you get 280.584 ≈ 280.6 ![m^2](https://tex.z-dn.net/?f=m%5E2)
you can also use the regular hexagon area formula instead of finding the individual area and multiplying by 6: ![\frac{3\sqrt{3} }{2} *a^2](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Csqrt%7B3%7D%20%7D%7B2%7D%20%2Aa%5E2)
Answer:
Male=21 Female=14
Step-by-step explanation:
So the problem would be (f)+(f+7)=35
first you would subtract 7 from 35
Now you have (f)+(f)=28 or 2f=28
Then you divide both sides by two
f=14
and since we know there is 7 more males then the answer is
m=21
Answer: multiply x by 2 in the first equation and subtract the second equation
Step-by-step explanation:
To solve a system of linear equations by elimination method , our first step is to make its (either x or y) coefficient same.
For that we multiply a number to both sides of the equation not to only one term.
So by checking all the given options it is pretty clear that the last option is not applicable for elimination method because in this 2 is multiplied to only one term, which proceeds to loose the balance of the equation.
Thus , an INCORRECT step that will NOT produce a system with the same solution is "multiply x by 2 in the first equation and subtract the second equation
".
Answer:
(5 t ) cubed = 5 cubed . t cubed = 125 t cubed applies the power of a product rule to simplify (5 t) cubed ⇒ 3rd answer
Step-by-step explanation:
Let us revise some rules of exponents
×
=
×÷
= ![a^{m-n}](https://tex.z-dn.net/?f=a%5E%7Bm-n%7D)
= ![a^{m.n}](https://tex.z-dn.net/?f=a%5E%7Bm.n%7D)
=
. ![b^{m}](https://tex.z-dn.net/?f=b%5E%7Bm%7D)
To simplify ![(5t)^{3}](https://tex.z-dn.net/?f=%285t%29%5E%7B3%7D)
∵ 5t means 5 × t
∵ Both of them are cubed
- Use the 4th rule above
∴
= ![(5)^{3}.(t)^{3}](https://tex.z-dn.net/?f=%285%29%5E%7B3%7D.%28t%29%5E%7B3%7D)
∵ (5)³ = 5 × 5 × 5 = 125
∴
=
= 125 t³
(5 t ) cubed = 5 cubed . t cubed = 125 t cubed applies the power of a product rule to simplify (5 t) cubed
Answer:
31
Step-by-step explanation:
50 - 2-3-6-3-5 = 31